BASIS - Globaler Klimawandel und seine Folgen für Nordeuropa; Teil 1: Rentierhaltung und Forstwirtschaft in Nordskandinavien - Manfred Lange; Hasko Schneider (IWF (Göttingen), 2004)
(en)Climate change will have significant consequences for human and natural living conditions in Northern Europe. The quantification and evaluation of the impacts of climate change on Northern Scandinavia were the central goal of a project funded by the European Commission, the Barents Sea Impact Study (BASIS). The results of the project with regard to climate change impacts on reindeer herding and forestry are addressed in the first part of this documentary. The film focuses in particular on the competition and possible utilisation conflicts between these two sectors and considers if, how and to what extent climate change might influence these problems.